2008
DOI: 10.1590/s0021-75572008000700008
|View full text |Cite
|
Sign up to set email alerts
|

Plaqueta e leptina em adolescentes com obesidade

Abstract: Objective: To analyze the influence of obesity status on immune cell count and concentration of the hormones cortisol and leptin, in order to establish a relationship among the variables analyzed. Methods:We recruited 27 obese [body mass index (BMI) ≥ 95th percentile] and 21 non-obese (BMI ≤ 75th percentile) adolescent boys and girls, aged 15-19 years at the post-pubertal stage. BMI was calculated as body weight divided by height squared, and body composition was estimated by plethysmography in the Bod Pod TM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
10
0
6
Order By: Relevance
“…In addition, research has shown that adults and children with obesity have higher levels of leukocytes, mainly monocytes, compared with adults and children of normal weight [32-34]. Regarding increased platelet count in subjects with obesity, similar findings have been shown in other studies, where the platelet count is higher in teenagers and adults with obesity than normal weight subjects [35,36]. In relation to cytokines, it has been shown that interleukin-6 (IL-6) induces differentiation of megakaryocytes into platelets and that IL-6 is produced by adipose tissue [37,38].…”
Section: Discussionsupporting
confidence: 68%
“…In addition, research has shown that adults and children with obesity have higher levels of leukocytes, mainly monocytes, compared with adults and children of normal weight [32-34]. Regarding increased platelet count in subjects with obesity, similar findings have been shown in other studies, where the platelet count is higher in teenagers and adults with obesity than normal weight subjects [35,36]. In relation to cytokines, it has been shown that interleukin-6 (IL-6) induces differentiation of megakaryocytes into platelets and that IL-6 is produced by adipose tissue [37,38].…”
Section: Discussionsupporting
confidence: 68%
“…An estimation of fat depots are essential to better understand the effects of obesity on the health status, as fat distribution has been described as an important marker of inflammation and is directly linked to changes in cytokine concentrations and the platelet count ( 8 ) . Additionally, platelets, red blood cells (RBCs) and hemoglobin are associated with cardiorespiratory conditions ( 9 , 10 ) , the oxidative metabolism ( 11 ) , and cardiovascular events ( 12 ) in obese and non-obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Foschini et al ,26 when assessing 48 adolescents, 27 obese and 21 non-obese according to BMI, also reported no differences regarding the concentrations of leukocytes, neutrophils, lymphocytes, and monocytes. However, Zaldivar et al 3 have shown that obese children have a higher concentration of circulating leukocytes, particularly neutrophils, monocytes, and lymphocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Foschini et al ,26 ao avaliarem 48 adolescentes, sendo 27 obesos e 21 não obesos segundo o IMC, também não relataram diferença com relação às concentrações de leucócitos, neutrófilos, linfócitos e monócitos. Por outro lado Zaldivar et al ,3 demonstraram que crianças obesas apresentam maior concentração de leucócitos circulantes, em particular, neutrófilos, monócitos e linfócitos.…”
Section: Discussionunclassified